SURGICAL EXTIRPATION OF GIANT CELL FIBROMA OF THE TONGUE USING A COMBINATION OF 450NM AND 650NM DIODE LASER WAVELENGTHS: A CASE REPORT - Kusumo, Norman Tri; Tjiptoningsih, Umi Ghoni (M-Dental Education and Research Journal, 2025)
Background: Giant cell fibroma (GCF) is a benign fibrous oral lesion typically occurring on the gingiva or tongue. Surgical extirpation is the treatment of choice. The use of diode laser technology offers a minimally invasive alternative with enhanced patient comfort and improved healing outcomes. This case report describes the successful extirpation of a GCF on the tongue using a combination of 450 nm (blue) and 650 nm (red) diode laser wavelengths. Case Presentation: A 27-year-old female presented with a painless, slow-growing nodular lesion on the lateral border of the tongue, measuring approximately 0.8 cm in diameter.Patient declare no chronic systemic condition. Clinical and histopathological findings confirmed the diagnosis of giant cell fibroma. A combination diode laser device was employed, utilizing the 450 nm wavelength for precise cutting with minimal thermal damage, and the 650 nm wavelength for its biostimulatory effects and hemostasis. The procedure was completed under local anesthesia with minimal bleeding and no sutures required. Results: Postoperative healing was uneventful, with no complications, pain, or recurrence observed at 4-week and 12-week follow-ups. The patient reported high satisfaction regarding comfort and esthetic outcomes. Histopathological examination confirmed complete excision of the lesion. Conclusion: The combination of 450 nm and 650 nm diode laser wavelengths represents an effective and patient-friendly approach for the surgical management of giant cell fibroma. This technique offers precise cutting, reduced intraoperative bleeding, faster healing, and enhanced patient comfort.